AVALIAÇÃO DE NOVAS CULTIVARES DE AMENDOIM NA REGIÃO DO BOLSÃO SUL-MATO-GROSSENSE - PUPIM, Gabriel de Souza; SERON, Cássio de Castro; TENÓRIO, Kamila de Paula; DEZAN, Iris Mendes Namizaki; VENDRUSCOLO, Eduardo Pradi; MARTINS, Murilo Battistuzzi (ANAIS DO ENIC, 2025)
-